The Effects of Remittance on Economic Growth in Nepal - Lamsal, Mani Ratna (Nepalese Journal of Management Science and Research, 2023)
The cross-border movement of workers has increased with the enactment of economic liberalization policy, especially after the 1990s in Nepal and increasing globalization in the world. It opened the door to the Nepalese workers in abroad, making their remittance one of the prime sources of foreign exchange earning in Nepal. Consequently, solving the problem of unemployment, remittance become the major contributor in Nepalese economy accelerating overall economic growth of the country; it is the major source of financial savings and thereby investment and growth. Despite the increasing importance of remittance in Nepalese economy, the overall impact of remittance on economic growth has not been adequately explored yet. This paper analyzes the effects of remittances on the economic growth of Nepal. Previous studies have found mixed results regarding to impact of remittances on economy- i.e. positive effects as well as negative effects of remittance on economic growth. So, this paper examines which effect is predominant in Nepalese context. The multiple regression model (OLS) is employed in the study in order to identify the effects of remittances on economic growth of Nepal. The time series secondary data for 20 years, 2001-2020, are collected from various published sources. This study concludes that there is positive and significant relationship between remittance and economic growth in Nepal. The impacts of other control variables, government expenditure and export trade are also positive for growth. However, expenses made on human capital has lagged effect, making insignificant in short run. The government of Nepal and concerned agencies should provide skill development trainings for the Nepalese migrants to increase their income in host countries. Government should encourage migrants to send remittances only from formal banking channels. It even helps for capital formation, investment and economic growth. It also solves the liquidity crisis and foreign exchange constraints in the nation, promoting the infrastructure development on the nation.